Precision Medicine to Treat Advanced Gastroesophageal Adenocarcinoma: A Work in Progress - Gambardella, Valentina (J Clin Med, 2020)
Gastroesophageal adenocarcinoma (GEA) represents a heterogeneous disease and, when diagnosed as locally advanced or metastatic, it is characterized by poor prognosis. During the last few years, several molecular classifications have been proposed to try to personalize treatment for those patients diagnosed with advanced disease. Nevertheless, despite the great effort, precision medicine is still far from being a reality. The improvement in the molecular analysis due to the application of high throughput technologies based on DNA and RNA sequencing has opened a novel scenario leading to the personalization of treatment. The possibility to target epidermal growth factor receptor (HER)2, Claudine, Fibroblast Growth Factor Receptors (FGFR), and other alterations with a molecular matched therapy could significantly improve clinical outcomes over advanced gastric cancer patients. On the other hand, the development of immunotherapy could also represent a promising strategy in a selected population. In this review, we sought to describe the novel pathways implicated in GEA progression and the results of the molecular matched therapies.